Bond Graph Dynamic Modeling of Wind Turbine with Singly-feed Induction Generator - Kadiman, Sugiarto; Yuliani, Oni; Suwarti, Diah (Universitas Ahmad Dahlan, 2024)
This paper contributes to a modeling part of singly-fed induction generator (SFIG) systems driven by constant wind turbines of generation capacity of 2.5 kW. As a consequence of some physical domains present in wind turbine, that are aerodynamical, mechanical and electrical, the modeling of wind turbine is challenging; therefore, modeling based on physical techniques has a higher credibility in these conditions. One of these ways is Bond-Graph modeling those representations the systems developed from the law of conservation of mass and energy covering in the systems. Bond graph uses causal analysis which is a process for identifying and addressing the causes and effects of a problem; moreover, the model is presented visually so that they are easier and more user friendly. In this paper, modeling the parts of among blades, tower, gearbox, and induction generator are based on the bond-graph method. The blades are modeled based on aerodynamic force model, both tower and gearbox are modeled based on rigid components model, and generator is model based on hybrid mechanic-electric model. Then, all of parts are connected together to accomplish the entire model of wind turbine for simulation based on 20-Sim software. The proposed wind turbine is the 2.5 KW variable speed with three blades, two-mass gearbox, tower, and a singly-fed induction generator type which is used in small and isolated category power generation systems. The model consists of realistic parameters. Using the Bond-Graph modeling method makes it easier to know what is actually happening in the system, for example the direction of energy movement in the system. Simulation results point out better performance of wind turbine with singly-feed induction generator, namely a more constant output current under constant wind conditions compared to varying wind conditions.